Identification of Heat Shock Protein 90 (HSP90) Gene Family in Cocoa (Theobroma cacao L.) in Silico Study - Mustafidah, Qori'atul; Su'udi, Mukhamad; Pancaningtyas, Sulistyani (Indonesian Coffee and Cocoa Research Institute, 2025)
Heat Shock Protein 90 (HSP90) has an important role in regulating heat stress response, plant development control, and defense reactions. The HSP90 gene family has been extensively reported in numerous plant species, but studies on the HSP90 gene in cocoa (Theobroma cacao L.) remain lacking. Continuous global warming and the use of low-grade quality planting materials are the reasons for low cocoa productivity in Indonesia. Based on this, it is necessary to have good adaptability in cocoa as well as the development of new cultivars so that there is no decrease in cocoa productivity. This study aims to identify the HSP90 gene family in cocoa to recognize the HSP90 functioning in cocoa and provide the necessary information to characterize HSP90 at the genome level. Identification of the HSP90 gene family in T. cacao was carried out through analysis of TcHSP90 sequences obtained from various related databases. The results showed that a total of seven TsHSP90 genes are distributed into ten T. cacao chromosomes. Analysis of the TcHSP90 motif showed that HSP90 is conserved in each T. cacao gene. Cis-acting element analysis showed that TcHSP90 has important roles in growth and development as well as abiotic and hormonal stress responses including defense against pathogens. Phylogenetic analysis showed that TcHSP90 has a similar evolutionary distribution to A. thaliana and S. lycopersicum. The results of this study can be used as a scientific foundation and basic knowledge for the development of new T. cacao cultivars that are resistant to biotic and abiotic stresses by selecting suitable candidate genes for T. cacao breeding.